A twin study of Perthes disease - Metcalfe, D; Van Dijck, S; Parsons, N; Christensen, K; Perry, D (American Academy of Pediatrics, 2016)
Background Legg-Calvé-Perthes Disease (LCPD) is an idiopathic avascular necrosis of the femoral head. Its aetiology is poorly understood, although previous studies have implicated low birth weight and possible genetic determinants. The aim of this study was to identify potential birth weight and genetic associations with LCPD. Methods We extracted all twin pairs from the Danish Twin Registry (DTR) in which at least one individual had LCPD. The DTR captures every twin pair born alive in Denmark and those with LCPD were identified using health record linkage. Probandwise concordance was calculated to describe the likelihood that any given individual had LCPD if their co-twin was also diagnosed. Results There were 81 twin pairs; 10 monozygotic (MZ), 51 dizygotic (DZ), and 20 unclassified (UZ). There was no association between birth weight and being the affected co-twin. Four pairs (two dizygotic and two unclassified) were concordant for LCPD, which is greater than would be expected assuming no familial aggregation. There were no concordant MZ twin pairs. The overall probandwise concordance was 0.09 (95% CI 0.01-0.18): 0.00 for the MZ, 0.08 (95% CI 0.00-0.18) for the DZ, and 0.18 (95% 0.00-0.40) for the UZ twin pairs. Conclusions This study found evidence of familial clustering in LCPD but did not demonstrate a genetic component. The absolute risk that a co-twin of an affected individual will develop LCPD is low, even in the case of MZ twin pairs.